Synthesis and Bioactivity of Guanidinium‐Functionalized Pillar[5]arene as a Biofilm Disruptor. Issue 2 (8th December 2020) - Guo, Shuwen; Huang, Qiaoxian; Chen, Yuan; Wei, Jianwen; Zheng, Jun; Wang, Leyong; Wang, Yitao; Wang, Ruibing
Abstract: Due to the inherent resistance of bacterial biofilms to antibiotics and their serious threat to global public health, novel therapeutic agents and strategies to tackle biofilms are urgently needed. To this end, we designed and synthesized a novel guanidinium‐functionalized pillar[5]arene (GP5) that exhibited high antibacterial potency against Gram‐negative E. coli (BH101) and Gram‐positive S. aureus (ATCC25904) strains. More importantly, GP5 effectively disrupted preformed E. coli biofilms by efficient penetration through biofilm barriers and subsequent destruction of biofilm‐enclosed bacteria. Furthermore, host–guest complexation between GP5 and cefazolin sodium, a conventional antibiotic that otherwise shows negligible activity against biofilms, exhibited much enhanced, synergistic disruption activity against E .  coli biofilms, thus providing a novel supramolecular platform to effectively disrupt biofilms. Abstract : Guanidinium‐functionalized pillar[5]arene (GP5) exhibited antibacterial activity against both Gram‐negative E. coli and Gram‐positive S. aureus bacterial strains. More significantly, it showed strong biofilm‐disrupting activity against preformed E. coli biofilms. Host–guest complexation between GP5 and a conventional antibiotic, cefazolin sodium, provides a supramolecular strategy for synergistically enhanced disruption of bacterial biofilms (see picture).